ANALISIS KENAIKAN HARGA KEDELAI TERHADAP PENDAPATAN AGROINDUSTRI TAHU DAN TEMPE DI KELURAHAN KEKALIK JAYA KECAMATAN SEKARBELA KOTA MATARAM - Sri Maryati; Mega Fitri; Ibrahim Ibrahim (Fakultas Pertanian Universitas Mataram, 2023)
This study aims to analyze the income of tofu and tempeh agro-industry. This study used a descriptive method with the unit of analysis being businesses that produce tofu and tempeh in Kekalik Jaya Village, Sekarbela District, Mataram City. The research locations were chosen, namely the Kekalik Gerisak, East Kekalik and Kekalik Kijang neighborhoods by purposive sampling in Kekalik Jaya Village, Sekarbela District, Mataram City. The number of artisan respondents was determined by quota as many as 30 respondents and the respondents were taken using the